2022
DOI: 10.1049/cvi2.12113
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian guided IoU: A better metric for balanced learning on object detection

Abstract: Most anchor‐based detectors use intersection over union (IoU) to assign targets to anchors during training. However, IoU did not pay enough attention to the proximity of the anchor's centre to the centre of the truth box, resulting in two issues: (1) the most slender objects were given just one anchor, resulting in insufficient supervision information for slender objects during training; (2) IoU cannot accurately represent the degree of alignment between the feature's receptive field at the anchor's centre and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…We compared the Intersection over Union (IoU), the Distance Intersection over Union (DIoU) [10], and the Generalized Intersection over Union (GIoU) [11]to calculate the occlusion of the target and found that these intersection over union methods are more suitable for target detection, but not very suitable for representing the degree of target occlusion. For the representation of occlusion, unlike the IoU used by algorithms like ImprAsso [12], we use occlusion degree to represent the situation of the target being occluded, that is, the ratio of the occluded area of the target to the total area of the target.…”
Section: Occlusion Awarenessmentioning
confidence: 99%
“…We compared the Intersection over Union (IoU), the Distance Intersection over Union (DIoU) [10], and the Generalized Intersection over Union (GIoU) [11]to calculate the occlusion of the target and found that these intersection over union methods are more suitable for target detection, but not very suitable for representing the degree of target occlusion. For the representation of occlusion, unlike the IoU used by algorithms like ImprAsso [12], we use occlusion degree to represent the situation of the target being occluded, that is, the ratio of the occluded area of the target to the total area of the target.…”
Section: Occlusion Awarenessmentioning
confidence: 99%
“…Sementara itu, data kebenaran dasar region objek bergerak yang harus dideteksi kuantil abu-abu. Selain itu, telah dilakukan pula pengujian pendeteksian objek bergerak memakai pendekatan tumpang tindih area hasil deteksi dan ground truth area yang harus dideteksi per sampel [18]. Berdasarkan pengujian ini, kuantil abu-abu nomor 3 pada sampel ke-1 mendapatkan IoU sebesar 0.85; kuantil abu-abu nomor 4 pada sampel ke-2 mendapatkan IoU sebesar 0.8; kuantil abu-abu nomor 4 pada sampel ke-3 mendapatkan IoU sebesar 0.9; kuantil abu-abu nomor 4 pada sampel ke-4 mendapatkan rata-rata IoU sebesar 0.9; kuantil abu-abu nomor 1 pada sampel ke-5…”
Section: Hasil Dan Pembahasanunclassified